Dissection of the genetic loci for grain hardness and variation of the key genes in common wheat (Triticum aestivum L.) - Jinna Hou; Pengge Sun; Pei Yan; Shenghui Geng; Wenxu Li; Maomao Qin; Ziju Dai; Baoming Tian; Zhengqing Wu; Zhengfu Zhou; Changwen Li; Zhensheng Lei (Current Plant Biology)
Identification of genetic loci for grain hardness was widely concerned by geneticists and breeders. Heretofore numerous genetic loci (genes) associated with grain hardness were detected in crops by previous studies. However, the genetic network and molecular mechanism for hardness control have not been extensively elucidated in wheat. In the present study, an association population consisted with 207 wheat accessions was planted across three years and the grain hardness index (GHI) of each accession was measured. The genetic loci associated with GHI were dissected based on a high-throughput SNPs map through genome-wide association study (GWAS). Finally, eight QTL, which explained 8.29 % – 14.59 % of the phenotypic variation, were revealed on chromosomes 1 A, 1B, 3 A, 3B, 5 A, 5B and 5D (2). The previously reported major genes for GHI, Pina and Pinb, were anchored in Qghi.5D-1, which was repeatedly detected under all environments (BLUP included). The haplotypes of Pina and Pinb were discriminated in the association population. Totally, six haplotypes were identified and among them the haplotypes Pina-D1a/PinbD1b (56.77 %) and Pina-Dla/Pinb-D1a (31.25 %) accounted for the highest proportion. Addtionally, a novel haplotype, Pina-null/Pinb-null, was detected in var. ‘Longfumai4hao’. The novel haplotype caused by a large fragment (about 26 Kb) deletion spanning Pina and Pinb genomic region. Furthermore, six KASP markers were developed, among which four were used to discriminate haplotypes of Pina and Pinb and two were developed from the peak SNPs of the major QTL located on 1 A and 1B, respectively. The present results elucidated genetic loci for grain hardness in wheat, not only provide novel genes and germplasms for appropriate hardness wheat breeding, but also assist to reveal the molecular mechanism under grain hardness regulation and improve end-use quality in wheat.